Feminilidade, corpo e beleza numa sociedade capitalista–patriarcal-midiatizada: um estudo de representações sociais - Cezario, Isabela Gomes (2022)
Among the oppressions suffered by women, which are constituted as agendas of feminist struggles, can be included the social imposition of standards to female bodies and behaviors. In a society that aims at profit and capital accumulation, it is safe to say that social relations are not randomly defined, but always involve power strategies. It becomes necessary, therefore, to analyze the possible strategies of domination and manipulation of women through discourses that are apparently libertarian and claiming, but that in practice have the purpose of maintaining the old submissions and violence that sustain the capitalist system through the propagation of standards of female bodies and unattainable aesthetics. The present research aimed to investigate social representations of the body, female beauty, and gender among women aged 18 and older, through a quantitative, descriptive study. Based on assumptions of the Theory of Social Representations, in general, and the Theory of the Central Core (TNC), specifically, a questionnaire was applied to 205 women of different ages, education and occupation. The instrument included a block of sociodemographic data and three questions of free evocation whose inductive terms were: being a woman, beautiful woman, and female body. Additionally, after each free association question, there were two questions, one about the most important word among those mentioned and why, and another with a positive or negative value assignment to the words presented. The data organization and analysis occurred with the help of OpenEvoc software, which offers support resources for data collection, processing, analysis, and visualization. In general, it was identified that women still associate beauty and female body with socially valued physical characteristics, such as Thin, Standard and Body (elements of the central core of beautiful woman) and Breast, Beauty, Thin, Objectified and Curves (elements of the central core of female body), showing social representations whose contents are close to conceptions based on Documento assinado digitalmente conforme descrito no(s) Protocolo(s) de Assinatura constante(s) neste arquivo, de onde é possível verificar a autenticidade do mesmo. 9 machismo, patriarchy and capitalist logic. However, in relation to the social representations of femininity/being a woman, despite still bringing contents that to some extent are sustained in traditional logic, it was structured around the elements (strength, fight, and warrior) that indicate meanings that point to the feminine potential in this context of control, oppression, and inequality. It is hoped that the findings of this dissertation will serve as triggers for new investigations, deepening some of the questions whose analysis we have tried here to at least outline.